ASSESSMENT OF FACTORS INFLUENCING THE CHOICE AND USE OF TEMPORARY CONTRACEPTIVE METHODS FOR BIRTH SPACING AMONG MARRIED WOMEN IN RURAL TRIVANDRUM - Dr Parvathy Mini Pradeep
Introduction: There is near universal awareness of limiting (sterilization) and spacing (IUD, Pills and Condom) techniques among women in Kerala, however the practice varies. According to DLHS-3 report, there is still 7.1% unmet need for spacing and it is 21.9% for women with 1 child. This study aims to find the contraceptive use among young married women between ages 20 – 29 years and also to find the factors that influence the choice and use of temporary contraceptives for birth spacing. Methods: A community based cross sectional study was conducted in 3 block panchayats in rural parts of Trivandrum district. A total of 294 women (between 20-30 years, who were currently married and not yet taken permanent methods of contraception) were interviewed for the study. An interview schedule was created using socio demographic and other factors which was then translated to Malayalam which was used for data collection. Results: Current temporary contraceptive usage was found out to be 24.1% .It is significantly affected by greater age at marriage (p=0.001), college education (p=0.021), employment (p=0.014), ability to choose their own employment (p=0.065), Christian community (p=0.032). In the study, 42.5% had ever used any contraceptives. This was affected by same factors but also others like higher socioeconomic status (p=0.007), motivation by family members (p=0.046), desire to have more than 1 child (p=0.057) and having only 1 child (p=0.085). By logistic regression, age at marriage (OR-2.44, p-0.006), religion (OR-2.20, p-0.020) were found as significant factors in deciding current contraceptive usage when adjusted for other factors. Conclusion: Age at marriage, education and religious beliefs affects the temporary contraceptive usage. Women who are motivated by family members and with ability to raise opinion about themselves also have increased usage. The general awareness about emergency contraceptives and injectable form of contraceptive is low compared to other methods.